Condensed matter - Srivastava, S K (World Scientific, 1995)
Includes bibliographical references.; This book deals with different aspects of the structure and properties of disordered materials. Whenever the normal state of matter is affected by internal or external agencies and new states are developed, it is generally observed that the new materials possess disordered structures. However, some characteristics (such as the electronic and ionic) remain similar to those of crystalline solids. Such isotropic materials are also termed disordered solids.This book surveys the physics of materials like non transition–transition metals and alloys in their solid and liquid phases, liquid-amorphous solids and materials with super structures like fullerene lattices etc. The advancements in these materials which possess unusual physical properties provide exciting possibilities for technology and industry. Up-to-date investigations about theoretical and experimental techniques are presented here. The reviews on different materials were prepared by renowned experts in the corresponding areas